Nonsymptomatic myocardial bridge causing systolic total narrowing of circumflex artery - Aksoy, Fatih (J Saudi Heart Assoc, 2018)
Myocardial bridge is defined as the narrowing of any coronary artery segment in systole but a normal diameter in diastole. It is most frequently seen on left anterior descending (LAD) artery. Left circumflex artery (LCx) is very rare. A 62 year-old male patient presented with severe, squeezing chest pain. The electrocardiogram showed T wave inversion in V1–V4 and ST depression in DII, DIII, aVF. Coronary angiography showed complicated lesion on after S2 branches of LAD and myocardial bridge causing 100% systolic narrowing of fourth obtus marginal branch of LCx. Bare metal stent was placed to LAD lesions with no residual occlusion. The patient was discharged with beta-blocker therapy. He had no recurrent chest pain during six months of follow-up.